(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
This article consists in an account about the author’s, Clorys Daly, pioneering trajectory in traditionally male-dominated spaces; from the creation of the first puppetry arts festivals in Brazil, through the founding of the Brazilian Puppetry Association (ABTB), the Bem-Me-Quer Marionette Circus, up to present days. Clorys retells how her mother was an inspirational woman and discusses the perception of her time on her work as a woman in theater and puppetry as well as the harassment suffered to conquer her space. In 2016 at age 82 Clorys became an Honorary Citizen of Rio de Janeiro City for her services to puppetry. In 2020 at age 86, Clorys states her motivation to continue to be active in puppetry arts. She concludes with her wishes and hopes for new generations. This work seeks to stimulate new generations of female puppeteers and producers to keep opening and fighting for their spaces in the puppetry arts.